DNA Methylation Analysis to Unravel Altered Genetic Pathways Underlying Early Onset and Late Onset Neonatal Sepsis. A Pilot Study - Lorente-Pozo, Sheila; Navarrete, Paula; Garzón, María José; Lara-Cantón, Inmaculada; Beltrán-García, Jesús; Osca-Verdegal, Rebeca; Mena-Mollá, Salvador; García-López, Eva; Vento, Máximo; Pallardó, Federico V.; García-Giménez, José Luis (Frontiers in Immunology, 2021)
Background: Neonatal sepsis is a systemic condition widely affecting preterm infants and characterized by pro-inflammatory and anti-inflammatory responses. However, its pathophysiology is not yet fully understood. Epigenetics regulates the immune system, and its alteration leads to the impaired immune response underlying sepsis. In particular, DNA methylation may contribute to sepsis-induced immunosuppression which, if persistent, will cause long-term adverse effects in neonates. Aims: To analyze the methylome of preterm infants in order to determine whether there are methylation marks that may shed light on the pathophysiology of neonatal sepsis. Methods: Prospective observational cohort study performed in the neonatal intensive care unit (NICU) of a tertiary care center. Eligible infants were premature with less than 32 weeks of gestation admitted to the NICU with suspicion of sepsis. The methylome analysis was performed in DNA from blood using Infinium Human Methylation EPIC microarrays to uncover methylation marks. Results: Methylation differential analysis revealed an alteration of methylation levels in genomic regions involved in inflammatory pathways which participate in both the innate and the adaptive immune response. Moreover, differences between early and late onset sepsis as compared to normal controls were assessed. Conclusions: DNA methylation marks can serve as a biomarker for neonatal sepsis and even contribute to differentiating between early and late onset sepsis. Furthermore, methylation marks may help to clarify the biological pathways underlying EOS and LOS and therefore contribute to prevent life-threatening complications during neonatal sepsis.